Resistant starch and type 2 diabetes mellitus: Clinical perspective - Min Kyung Kim; Juri Park; Doo‐Man Kim (Journal of Diabetes Investigation, 2024)
Abstract The immediate and well‐documented benefits of carbohydrate restriction include improved glycemic control in individuals with diabetes mellitus. Starch, a significant source of carbohydrates, is categorized as rapidly digestible, slowly digestible, or resistant starch (RS). RS, which is a non‐viscous fermentable fiber, has shown promise in animal studies for antidiabetic effects by improving glucose metabolism. Although the exact mechanism by which RS affects glucose metabolism remains unclear, it is expected to positively impact glucose tolerance and insulin sensitivity. The fermentation of RS by colonic microbiota in the large bowel produces short‐chain fatty acids, which exert multiple metabolic effects on glucose regulation and homeostasis. Moreover, RS may influence glucose metabolism via bile acid modulation, independent of its fermentation. Diets rich in RS could aid in blood glucose homeostasis. However, it is uncertain whether they can alter the metabolic pathology associated with glucose regulation. In essence, RS has the potential to lower postprandial glucose levels similarly to a low‐glycemic index diet. Yet, its efficacy as a medical nutrition therapy for type 2 diabetes needs further investigation. To confirm the role of RS in glycemic control and to possibly recommend it as an additional dietary approach for people with type 2 diabetes mellitus, a well‐designed, large‐scale intervention is required.